Copper-catalyzed regio- and stereoselective hydroallylation of thioalkynes with allylboronates: a facile and convenient synthesis of 1, 4-dienes. Issue 21 (20th May 2015) - Kong, Wei; Che, Chao; Kong, Lichun; Zhu, Gangguo
Graphical abstract: Abstract: A Cu-catalyzed, highly regio-, and stereoselective hydroallylation of thioalkynes has been developed with allylboronates as the allylating reagents, providing stereodefined 1, 4-dienyl sulfides in good to excellent yields under very mild reaction conditions. The resulting products can been smoothly converted into skipped dienes by a Ni-catalyzed coupling of C–S bonds with Grignard reagents, thus offering a novel efficient method for the regio- and stereoselective synthesis of 1, 4-dienes.